Life Sciences Capital Fund : Malaysia Case Study - World Bank (Washington, DC, 2014)
The Malaysian Life Sciences Capital Fund (MLSCF) is a venture capital fund based in Kuala Lumpur, Malaysia. MLSCF has succeeded in transferring biotechnologies from more-developed to less developed countries. The specific technologies of interest to the fund have the potential to significantly improve farm productivity. Two organizations, one public and the other private, co-manage MLSCF. They are the Malaysian Technology Development Corporation (MTDC), a government organization, and Burrill and Company, a San Francisco-based merchant bank. The fund manages $150 million in committed capital. The concept underlying the fund is to pursue science without borders through a process of open innovation. Open innovation greatly reduces the transaction costs of technology transfer.